Análisis de la demanda de actividades turísticas y ocio nocturno en la ciudad de Babahoyo - Correa Correa, Juliana Sofía (2020)
The purpose of this case study is to analyze the demand for nightlife tourism activities in the city of Babahoyo. With this, it will be possible to identify the tastes of the inhabitants and their surroundings and provide market information to the providers of these services in the canton, allowing them to adapt and improve their spaces for night-time activities so that they meet the needs of the tourists who come to this beautiful canton. The design of this research work follows a quantitative approach. Analytical and observational methods were used. The development of a bibliographic and exploratory research was included. A survey was conducted aimed at the demand for this type of activities in the canton, including questions, mostly closed, to determine the profile of visitors to these tourist activities. Among the main findings, it is observed that the Babahoyense population and tourists are uninformed about the night activities that the canton offers. This strongly harms tourism since its inhabitants are looking for these services abroad and do not support their own.